Mobile phones represent a pathway for microbial transmission: A scoping review. Issue 35 (May 2020) - Olsen, Matthew; Campos, Mariana; Lohning, Anna; Jones, Peter; Legget, John; Bannach-Brown, Alexandra; McKirdy, Simon; Alghafri, Rashed; Tajouri, Lotti
Abstract: Background: Mobile phones have become an integral part of modern society. As possible breeding grounds for microbial organisms, these constitute a potential global public health risk for microbial transmission. Objective: Scoping review of literature examining microbial's presence on mobile phones in both health care (HC) and community settings. Methods: A search (PubMed&GoogleScholar) was conducted from January 2005–December 2019 to identify English language studies. Studies were included if samples from mobile phones were tested for bacteria, fungi, and/or viruses; and if the sampling was carried out in any HC setting, and/or within the general community. Any other studies exploring mobile phones that did not identify specific microorganisms were excluded. Results: A total of 56 studies were included (from 24 countries). Most studies identified the presence of bacteria (54/56), while 16 studies reported the presence of fungi. One study focused solely on RNA viruses. Staphylococcus aureus, and Coagulase-Negative Staphylococci were the most numerous identified organisms present on mobile phones. These two species and Escherichia coli were present in over a third of studies both in HC and community samples. Methicillin-resistant S. aureus, Acinetobacter sp., and Bacillus sp. were present in over a third of the studies in HC settings. Conclusions: While this scoping review of literature regarding microbial identification on mobile phones in HC and community settings did not directly address the issue of SARS-CoV-2 responsible for COVID-19, this work exposes the possible role of mobile phones as a 'Trojan horse' contributing to the transmission of microbial infections in epidemics and pandemics.